2010
DOI: 10.1007/s10544-010-9476-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evaluation of cell differentiation after the isolation of single cells by a femtosecond laser-induced impulsive force

Abstract: When nerve growth factor (NGF) is interacted with PC12 cells derived from rat pheochromocytoma, they are partially differentiated into neuron-like cells with neurites. In this work, PC12 cells differentiated by NGF were selectively isolated using a localized impulsive force in a μm-scale area, which was generated by focusing an infrared femtosecond laser into a cell culture medium. In order to evaluate the ability of the isolation method, differentiated and undifferentiated cells were isolated and their morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…By the quantification of the impulsive force, we were able to estimate intercellular breaking force of a leukocyte and an epithelial cell without modifying the culture system for the measurement. 7 We demonstrated that the impulsive force is practically available as an external force to manipulate the single cells 8,9 and to inject biomolecules into single cells. 10 For establishing applications, controllability of the impulsive force should be confirmed.…”
Section: Takanori Iino and Yoichiroh Hosokawamentioning
confidence: 99%
“…By the quantification of the impulsive force, we were able to estimate intercellular breaking force of a leukocyte and an epithelial cell without modifying the culture system for the measurement. 7 We demonstrated that the impulsive force is practically available as an external force to manipulate the single cells 8,9 and to inject biomolecules into single cells. 10 For establishing applications, controllability of the impulsive force should be confirmed.…”
Section: Takanori Iino and Yoichiroh Hosokawamentioning
confidence: 99%
“…By targeting the femtosecond laser in the vicinity of a target cell, this technique dissociates the adherent cell of interest from the culture scaffold (8)(9)(10)(11). This irradiation does not appear to damage cellular functions such as cell growth or cell differentiation (10,11).…”
mentioning
confidence: 99%
“…Another trial which we introduce here is to elucidate effects of the impulsive force on animal cell differentiation using PC12 cells derived from rat pheochromocytoma. A schematic illustration of our experimental procedure 100 is given in Figure 36. When nerve growth factor is interacted with PC12 cells, they are partially differentiated into neuron like-cells with neuritis.…”
Section: Manipulation and Processing Of Living Cells By Femtosecond Lmentioning
confidence: 99%